How do we know that our patients have benefitted from our ENT/Audiological interventions?: presented at the Annual Meeting of ADANO 2016 in Berlin - Hall, Deborah A.; Kitterick, Pádraig T.; Heffernan, Eithne; Fackrell, Kathryn; Lucas, Laura; Ferguson, Melanie (Lippincott Williams & Wilkins, 2018)
This short review article gives an introduction to some of the fundamental concepts and challenges facing measurement in hearing healthcare practice and research. The impact of hearing loss almost always extends beyond the sensory impairment itself, even when the measured degree of audiometric loss is mild. Yet, going beyond audibility, into the realm of measuring impact, takes us into a much more complex and less well-defined space. How does one therefore best measure the therapeutic benefit for evaluating efficacy or for clinical practice audit? Three case studies illustrate approaches to overcome such challenges. Each example highlights the importance of thinking critically about what it is one is seeking trying to measure, rather than selecting a questionnaire instrument based simply on its popularity or accessibility. We conclude by highlighting the important role that clinicians can play in collecting clinical data about their preferred instruments so that we have some evidence to inform decisions about good practice (content validity etc). We would also strongly support open data sharing as we believe that this is one of the best ways to make the most rapid progress the field.